Dysregulation of Complement Activation and Placental Dysfunction: A Potential Target to Treat Preeclampsia? - Pierik, E.; Prins, Jelmer R.; van Goor, Harry; Dekker, Gustaaf A.; Daha, Mohamed R.; Seelen, Marc A. J.; Scherjon, Sicco A. (Frontiers in Immunology, 2020)
Preeclampsia is one of the leading causes of maternal and neonatal mortality and morbidity worldwide, affecting 2-8% of all pregnancies. Studies suggest a link between complement activation and preeclampsia. The complement system plays an essential role in the innate immunity, leading to opsonization, inflammation and elimination of potential pathogens. The complement system also provides a link between innate and adaptive immunity and clearance of immune complexes and apoptotic cells. During pregnancy there is increased activity of the complement system systemically. However, locally at the placenta, complement inhibition is crucial for the maintenance of a normal pregnancy. Inappropriate or excessive activation of the complement system at the placenta is likely involved in placental dysfunction, and is in turn associated with pregnancy complications like preeclampsia. Therefore, modulation of the complement system could be a potential therapeutic target to prevent pregnancy complications such as preeclampsia. This review, based on a systematic literature search, gives an overview of the complement system and its activation locally in the placenta and systemically during healthy pregnancies and during complicated pregnancies, with a focus on preeclampsia. Furthermore, this review describes results of animal and human studies with a focus on the complement system in pregnancy, and the role of the complement system in placental dysfunction. Various clinical and animal studies provide evidence that dysregulation of the complement system is associated with placental dysfunction and therefore with preeclampsia. Several drugs are used for prevention and treatment of preeclampsia in humans and animal models, and some of these drugs work through complement modulation. Therefore, this review further discusses these studies examining pharmaceutical interventions as treatment for preeclampsia. These observations will help direct research to generate new target options for prevention and treatment of preeclampsia, which include direct and indirect modulation of the complement system.